2022
DOI: 10.3389/fvets.2021.782149
|View full text |Cite
|
Sign up to set email alerts
|

Lesion Material From Treponema-Associated Hoof Disease of Wild Elk Induces Disease Pathology in the Sheep Digital Dermatitis Model

Abstract: A hoof disease among wild elk (Cervus elaphus) in the western United States has been reported since 2008. Now present in Washington, Oregon, Idaho, and California, this hoof disease continues to spread among elk herds suggesting an infectious etiology. Causing severe lesions at the hoof-skin junction, lesions can penetrate the hoof-horn structure causing severe lameness, misshapen hooves, and in some cases, sloughed hooves leaving the elk prone to infection, malnutrition, and premature death. Isolated to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…As a species that is regularly transferred between institutions and rewilded in Europe, preventing the transmission of infectious diseases is of particular importance ( 43 ). The rapid spread of Treponema -associated hoof disease in free-living elk illustrates the difficulty of controlling this infectious hoof disease once it has established in the population ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a species that is regularly transferred between institutions and rewilded in Europe, preventing the transmission of infectious diseases is of particular importance ( 43 ). The rapid spread of Treponema -associated hoof disease in free-living elk illustrates the difficulty of controlling this infectious hoof disease once it has established in the population ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCR for Treponema medium, Treponema pedis, Treponema phagedenis, Treponema vincentii , Treponema denticola, Treponema brennaborense and Fusobacterium necrophorum was performed on n = 158, including healthy, lesion and contralateral samples, in a two-stage nested PCR assay as previously described [ 1 , 17 , 18 ]. Positive controls were genomic DNA purified from each respective bacterial species.…”
Section: Methodsmentioning
confidence: 99%
“…Recent meta-analysis of bovine digital dermatitis microbiota concluded that bacteria from the Treponema genus were highly abundant in bacterial populations in DD positive skin samples as compared to DD negative skin samples, implicating the genus as a core pathogen for lesion development [ 23 ]. There is evidence from numerous studies that DD and DD-like diseases (CODD & TAHD) are polymicrobial and that a core consortium of Fusobacterium spp., Bacteroides spp., Porphyromonas spp., and Mycoplasma spp., may also contribute to lesion development, although reported bacterial population abundances within lesions differ between published studies [ 1 , 9 , 11 , 13 , 17 , 23 , 24 ]. Molecular techniques have confirmed observations of spirochetal bacteria infiltrates deeper within the lesions, with cocci and fusiform rods forming matts on the outer epithelium in silver-stained tissue sections [ 1 , 4 , 25 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Wilson-Welder et al [ 27 ] inoculated crossbred sheep with bovine derived DD inoculum and achieved an 88% induction over a 28-day protocol, and contagious ovine digital dermatitis was induced in 15 of 30 experimental sheep [ 28 ]. Most recently, Wilson-Welder et al [ 29 ] using lesion material obtained from wild elk induced treponeme-associated hoof disease in sheep by way of a sheep DD model. To date there have been no published reports that have attempted to experimentally induce DD in beef cattle.…”
Section: Introductionmentioning
confidence: 99%